Study of the Level of Understanding of Parents towards Their Children Curriculum in Vocational Schools - Sunawar, Aris (INVOTEC, 2017)
The family is the smallest part in the education unit, the role of parents as educators of children is not stopped just when children start to school and handed over all their children to school education. While the curriculum in 2013, which is based morals, that assessment is not just a numbers, but also the record of the school to the child's progress. To find out how much parents knowledge of the curriculum that is being taken by their child, more research needs to be done, one method is a survey to the parents whose children are still at the high school / vocational randomly either public or private. Questions in the survey is the essence and purpose of the curriculum and the extent to which parents learn and understand the principle of the curriculum as well as participation in their children's education during school. From the results obtained that 83% of parents claimed to already know the competencies that will be owned by his son, and 80% of them have a desire to participate in curriculum development of their children. One of the obstacles they are to participate in the development is the time and their competence in curriculum development. So if parents can also be involved in the curriculum development should been socialized continuously from the school authorities and parents . Who are willing to help the development of the curriculum to get the formula of what competency is needed most and ready to work after graduation.